Determinants of acceptance in digitalizing internal corporate governance mechanisms: the case of the Annual General Meeting - NEJJAR, WAFAE NADA; HAZEM, LOUBNA (Revue du contrôle, de la comptabilité et de l’audit, 2024)
Information and communication technologies are now an integral part of organizational management techniques. The objective of our research is to clarify the determinants of acceptance of videoconferencing technologies for the holding of general assembly meetings in the particular context of the state of health emergency, caused by the Covid-19 pandemic. To this end, we adopt a theoretical approach by the UTAUT model adapted to our study context. This choice is justified by the fact that it exceeds other theoretical models of ICT adoption, with an R² variance that exceeds 70%. Following a comprehensive survey administered to participants in the general assembly meetings (managers, shareholders and statutory auditors), our results were then retained for analysis on the SmartPLS software using the structural equation approach. The results obtained show that expected performance is the only variable that determines the intention to use. Furthermore, perceived risk, social influence and effort expectancy have no significant effect on the adoption of this technology. Key words: «Determinants of ICT acceptance»; «UTAUT»; «General Assembly»; «Covid-19»; «SmartPLS software».